Association of Metabolic Syndrome with Albuminuria in Diabetes Mellitus Type 2 - Thamrin, Husin; Sutjahjo, Ari; Pranoto, Agung; Soelistijo, Soebagijo Adi (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2019)
Background : Metabolic syndrome is a risk factor for cardiovascular disease as well as the occurrence of chronic kidney disease. According to the IDF, the metabolic syndrome is diagnosed when central obesity obtained with 2 or more metabolic abnormalities that include impaired glucose metabolism, increased blood pressure, hypertriglyceridemia, and low HDL-C. Several previous studies reported an significant association found between the metabolic syndrome with albuminuria. In Indonesia, the association of metabolic syndrome with albuminuria in type 2 diabetes have not been.reported.Objectives : To investigate the association of metabolic syndrome with albuminuria in type 2 diabetes patients.Methods : This is an analytic observational study, cross-sectional design in type 2 diabetes mellitus patients and we studied 131 subjects. Criteria metabolic syndrome according to IDF consensus and albuminuria assessed using the ACR method and the classification of albuminuria was based on consensus of Perkeni 2006. As for Statistical analysis using spearman correlation and Mann-whitney test. Significance level used was 0.05.Results : Of the 131 type 2 diabetes patients with metabolic syndrome were found normoalbuminuria proportion 65.4%, microalbuminuria 27.1% and macroalbuminuria 7.5%. Obtained a significant association between systolic blood pressure with albuminuria, p = 0.000, r = 0.325. Fasting blood sugar with albuminuria, p = 0.01, r = 0.223. But not found significant association between diastolic blood pressure with albuminuria, p = 0.153, r = 0.125, waist circumference with albuminuria, p = 0.311, r = 0.089, low HDL with albuminuria p = 0.771, r = -0.025. Hypertriglyceridemia with albuminuria, p = 0.727 and r=0,031 Conclusion : The results of this study indicate a strong association between the components of metabolic syndrome, systolic blood pressure with albuminuria, and fasting blood sugar with albuminuria. Whereas diastolic blood pressure, waist circumference, low HDL, and hypertriglyceridemia were not found significant associations.